Morphodynamics of Fetch-Limited Beaches in Contrasting Environments - Freire, P. (2009)
Sandy beaches can be found in fetch-limited environments that are protected from ocean generated waves, as estuaries, lagoons, and backbarriers, and where fetch characteristics allow local wind-generated waves to develop and maintain a beach. The morphodynamics of these low-energy beaches present a peculiar behaviour and general open-ocean models are inappropriate for their study. The main objective of this work is the development of a fetch-limited beach classification scheme based on the relative importance of wave, tidal and river flow forcing. This objective was pursue through the study of the evolutionary pattern of two fetch-limited beaches located in two different Portuguese systems, Alfeite (in Tagus Estuary) and Ancão backbarrier (in Ria Formosa barrier system). Results show that both beaches display a typical fetch-limited profile, with a narrow reflective beach face and a wide dissipative tidal flat, and that profile shape exhibits small changes without a seasonal pattern typical of ocean beaches. At Alfeite, profile changes are restricted to the beach face and result from low-frequency extreme events (strong wind generated waves, Hs>0.5m). At Ancão, although major morphologic changes are also related to the beach face, which is typical behaviour of wave dominated beaches, sediment transport, mainly driven by tidal currents, extends through the entire profile. A tentative fetch-limited beach classification, based on the relative importance of wave and tide effects, is presented.